Recasting Classical and Contemporary Philosophies to Ground Peace Education (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Review Essay of James Page, Peace Education: Exploring Ethical and Philosophical Foundations (Charlotte, NC: Information Age Press, 2008)